Emerging investigator series: polymeric nanocarriers for agricultural applications: synthesis, characterization, and environmental and biological interactions. Issue 1 (20th December 2019) - Shakiba, Sheyda; Astete, Carlos E.; Paudel, Sachin; Sabliov, Cristina M.; Rodrigues, Debora F.; Louie, Stacey M.
Abstract : This review discusses polymeric nanocarriers for agrochemical delivery, from synthesis, characterization, and release, to benefits for agrochemical efficiency and sustainability. Abstract : Polymeric nanoparticles represent one major class of nanomaterials that has been proposed to improve the sustainability of agricultural operations by delivering organic agrochemicals such as pesticides more efficiently. Polymeric nanoparticles can improve efficiency through improved targeting and uptake, slow release, and lower losses of the chemicals, while also conferring the benefits of biodegradability and biocompatibility. This review provides a tutorial to environmental nanotechnology researchers interested in initiating research on the development and application of polymeric nanocarriers for delivery of agrochemicals, including pesticides and growth promoters for crops and antibiotics for livestock. In particular, this review covers the wider suite of methods that will be required beyond those typically used for inorganic metal or metal oxide nanoparticles, including synthesis of custom polymeric nanocarriers and characterization and tuning of agrochemical loading and release profiles. Benefits of polymeric nanocarriers are then discussed in terms of the physicochemical properties and fate and transport behaviors that contribute to higher efficiency and lesser environmental impacts compared to traditional (non-nano) formulations. Finally, opportunities for environmental nanotechnology researchers to collaborate with material scientists, microbiologists, and agricultural scientists to optimize the development of polymeric nanocarriers for agriculture are discussed.